Food as an element in developing tourist experiences. A case study of the Finnmark region in Northern Norway - Kristensen, Alita Dagmar (UiT The Arctic University of Norway, 2017)
The focus on food as a significant element and topic in tourism and tourists’ experiences has increased. How tourists experience food has changed together with tourists’ motivation and needs. Current findings indicate that tourists seek and expect to find local food experiences while travelling to a new destination. This thesis aims to build knowledge on how food as an element in tourism play a role for the tourism and hospitality industry, and their development of relevant tourist product concepts. The conceptual model of the push and pull factors, and the conceptual model of the tourist experience have been used as a tool of reflection, in order to analyze the topic studied. A case study of Finnmark, Northern Norway, was conducted in January 2017. In detail, this involved how general managers in the tourism industry experienced how food influenced the tourists’ experiences, as a supporting or as part of the peak experience. The findings in this thesis indicate that general managers in the tourism industry, in Finnmark, view local food as important symbols of the region. Herein, the tourist industry is giving priority to the development of food as a potential tourist attraction that can enhance the destination experience of Finnmark, either as a supporting or as part of the peak experience.